2016
DOI: 10.1016/j.ttbdis.2016.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of G protein-coupled receptor encoding sequences from the synganglion transcriptome of the cattle tick, Rhipicephalus microplus

Abstract: The cattle tick, Rhipicephalus (Boophilus) microplus, is a pest which causes multiple health complications in cattle. The G protein-coupled receptor (GPCR) super-family presents a candidate target for developing novel tick control methods. However, GPCRs share limited sequence similarity among orthologous family members, and there is no reference genome available for R. microplus. This limits the effectiveness of alignment-dependent methods such as BLAST and Pfam for identifying GPCRs from R. microplus. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Transcriptomes from the R. microplus gut (Heekin et al, 2013a), ovaries (Heekin et al, 2013b), and synganglion (Guerrero et al, 2016) were previously described. The transcriptome from the fore leg (Haller's organ) (4888 sequences) was obtained by similar methods to those described in Guerrero et al (2016).…”
Section: Organ-specific Transcriptomes From Rhipicephalus Microplusmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomes from the R. microplus gut (Heekin et al, 2013a), ovaries (Heekin et al, 2013b), and synganglion (Guerrero et al, 2016) were previously described. The transcriptome from the fore leg (Haller's organ) (4888 sequences) was obtained by similar methods to those described in Guerrero et al (2016).…”
Section: Organ-specific Transcriptomes From Rhipicephalus Microplusmentioning
confidence: 99%
“…Transcriptomes from the R. microplus gut (Heekin et al, 2013a), ovaries (Heekin et al, 2013b), and synganglion (Guerrero et al, 2016) were previously described. The transcriptome from the fore leg (Haller's organ) (4888 sequences) was obtained by similar methods to those described in Guerrero et al (2016). The R. microplus transcriptome nucleotide sequences were searched as databases against queries of protein sequences from the A. americanum proteomics analysis, using the tblastn command in BLAST+ version 2.2.31, with all parameters set at their default values.…”
Section: Organ-specific Transcriptomes From Rhipicephalus Microplusmentioning
confidence: 99%
“…Previous experiments in ticks indicated that prediction of GPCRs using transcriptome analysis might be a challenging task. As such, the transcriptome study of the bovine tick Boophilus microplus did not allow to detect the kinin receptor, a neuropeptide GPCR (Guerrero et al, 2016), which should be present (Holmes et al, 2000), underscoring the often low expression of GPCRs as a challenge for detection. Likewise, only two G proteins were identified in I. scapularis ticks and all were expressed at low to non-existent levels in legs (Josek et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The sialotranscriptome of A. variegatum (36), A. americanum (37)(38)(39), D. variabilis (39), I. scapularis (40,41), I. ricinus (42), D. andersoni Alarcon-Chaidez; (43) and R. appendiculatus (44) have been determined. R. microplus transcriptomes of larvae (45)(46)(47)(48)(49), engorged female gut (50), ovary (51), and synganglia (52) have been reported recently. The full-length coding sequences of numerous proteins and unique protein tick protein families have been described based in these analyses and their roles during host-parasite interaction described.…”
Section: Omics Approaches In Tick Vaccine Developmentmentioning
confidence: 97%